2014
DOI: 10.1103/physrevb.90.195409
|View full text |Cite
|
Sign up to set email alerts
|

First-principles and spectroscopic studies of Bi(110) films: Thickness-dependent Dirac modes and property oscillations

Abstract: The electronic structure of Bi(110) thin films as a function of film thickness is investigated by first-principles calculations, angle-resolved photoemission spectroscopy, and scanning tunneling microscopy. Energy minimization in the calculation reveals significant atomic relaxation and rebonding at the surface. The calculated surface energy for the relaxed structures indicates that films consisting of odd numbers of atomic layers are inherently unstable and tend to bifurcate into film domains consisting of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 32 publications
7
43
0
Order By: Relevance
“…[24] The Bi(110) structure is stabilized in the thinner films, while the transition to Bi(111) occurs at a critical thickness that is dictated by the substrate. [25] In the present study, the film thickness was ≤ 9 Å, with only the Bi(110) structure observed. The thickness was calibrated by measuring the core-level attenuation of Bi 5d 5∕2 peak of Bi2212 and sometimes expressed in units of bilayer (BL) corresponding roughly to ≈3.3 Å of Bi.…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…[24] The Bi(110) structure is stabilized in the thinner films, while the transition to Bi(111) occurs at a critical thickness that is dictated by the substrate. [25] In the present study, the film thickness was ≤ 9 Å, with only the Bi(110) structure observed. The thickness was calibrated by measuring the core-level attenuation of Bi 5d 5∕2 peak of Bi2212 and sometimes expressed in units of bilayer (BL) corresponding roughly to ≈3.3 Å of Bi.…”
Section: Resultsmentioning
confidence: 43%
“…[29] The dispersion of states along theΓ-M for the present film is shown in Figure 1c. A comparison with the reported theoretical calculations [24,25,29] suggests that the observed states correspond to the 2 and 3 BL Bi(110) films.…”
Section: Resultsmentioning
confidence: 55%
“…Bi and Sb have played the pivotal role in designing and developing topological condensed matter phases with protected electronic states, which can be largely attributed to their unique electronic properties, especially the strong spin-orbit coupling [1][2][3][4][5][6]. The electronic structure of Bi and Sb has been measured in several experiments by angle-resolved photoemission spectroscopy (ARPES) [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…). Ref [25]. discusses these symmetry issues for Bi films with odd-layer thicknesses in more detail and shows that -in contrast with graphene -the strong spin-orbit coupling in MBi is essential for creating Dirac cones in this system.…”
mentioning
confidence: 99%